The association between leisure-time physical activity and blood pressure changes from adolescence to young adulthood: Tehran Lipid and Glucose Study - Yari-Boroujeni, Reza; Farjad, Mohammad-Farid; Olazadeh, Keyvan; Cheraghi, Leila; Parvin, Parnian; Azizi, Fereidoun; Amiri, Parisa (Scientific reports, 2023)
The effectiveness of long-term leisure time physical activity (LTPA) on blood pressure (BP) changes is still under debate. Since adolescence lifestyle behaviors shape the adulthood health profile, this study aimed to investigate the sex-specific impact of LTPA on BP changes from adolescence to young adulthood. This longitudinal study uses the data of 1412 adolescents (52% females) aged 12–18 years through a median follow-up of 12.2 years in the Tehran Lipid and Glucose Study (TLGS) framework. LTPA was calculated using the reliable and valid Iranian version of the modified activity scale (MAQ), and BP was measured at least twice by trained physicians. The linear mixed model was used to examine the study variables, considering individual and intrapersonal differences during the study. The majority of participants consistently demonstrated insufficient LTPA throughout the follow-up assessments, ranging from 54.7 to 67.1% for males and 77.7–83.4% for females. Despite a declining trend in LTPA (β = − 2.77 for males and β = − 1.43 for females), an increasing trend was noticeable in SBP, DBP, and BMI (β = 1.38, β = 1.81, β = 0.97 for males, and β = 0.10, β = 0.20, β = 0.97 for females, respectively). The unadjusted model revealed a significant trend in all variables for both sexes, except for female BP (P = 0.45 for SBP and P = 0.83 for DBP). Using the adjusted model, no significant association was observed between LTPA and changes in BP over time in both sexes. Our study indicates no association between LTPA and BP changes from adolescence to young adulthood. Insufficient LTPA levels, particularly among Iranian females, are likely the primary factor. Further research is crucial to identify appropriate LTPA levels to promote cardiovascular health and implement targeted interventions to achieve optimal LTPA levels in the Iranian population.